Social Sustainability, Inclusive Cities and the Legacy of FIFA in Qatar: The Case of Education City - Shaikha Al-Wadaani; Jessica DuPlessis; Hira Amin; Khansa Chemnad; Evren Tok (Social Sciences)
Social sustainability, particularly in the form of inclusive cities, is high on the global agenda. One local manifestation working towards these goals in Qatar is Qatar Foundation for Education, Science, and Community Development’s Education City: a large campus with multiple schools, universities, communities, and cultural institutions, as well as home to one of the major stadiums of the FIFA World Cup Qatar 2022 tournament, hitherto the most accessible World Cup in history. This study is based on a survey that explores the experiences of people with and without disabilities in their interactions with Education City’s infrastructure, facilities, and services, as well as the legacy of hosting FIFA. It found that people’s experiences of social inclusion and belonging were positive given the multiple inclusive programs hosted by Education City and that hosting FIFA accelerated this shift. Yet, there is still significant room for improvement in the availability and quality of facilities, services with trained staff, clear communication, and advertisement and raising awareness of institutionalizing policies that reduce discrimination and stigma. Designing disability-inclusive cities is a complex grand societal challenge that requires intentional integration and constant monitoring and evaluation in an increasingly urbanized world. This is one of the first studies on Qatar and post-tournament legacy after a World Cup that prioritized accessibility.